Heme alters biofilm formation in Mycobacterium abscessus - Hadia Aftab; Jessica Samudio; Grace Wang; Lily Le; Rajesh K. Soni; Rebecca K. Donegan (Microbiology Spectrum)
ABSTRACT Mycobacterium abscessus (Mabs) is commonly found in the cystic fibrosis (CF) lung. During infection, Mabs can form biofilms in the lung which reduce both the ability of the immune response to clear infection and the effectiveness of antibiotic therapy. In the CF lung, heme and hemoglobin levels are increased and may provide both iron and heme to Mabs cells. In this work, we show that exogenous heme altered Mabs biofilm formation and measured the effects of exogenous heme on protein level and metabolism in Mabs. Our findings suggest that heme impacts iron homeostasis in Mabs and affects other aspects of its metabolism, highlighting the potential role of heme as a critical nutrient for Mabs growth and biofilm formation.IMPORTANCEMycobacterium abscessus (Mabs) is commonly found in the cystic fibrosis (CF) lung, where Mabs can form biofilms that can reduce the efficacy of antibiotics. During infection, the CF lung can have more than 10 times the extracellular heme than that of a healthy lung. We have found that extracellular heme can change the way Mabs cells grow and form biofilms, which may have implications for pathogenesis.